2(x-12)+13=4x+17

Simple and best practice solution for 2(x-12)+13=4x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-12)+13=4x+17 equation:


Simplifying
2(x + -12) + 13 = 4x + 17

Reorder the terms:
2(-12 + x) + 13 = 4x + 17
(-12 * 2 + x * 2) + 13 = 4x + 17
(-24 + 2x) + 13 = 4x + 17

Reorder the terms:
-24 + 13 + 2x = 4x + 17

Combine like terms: -24 + 13 = -11
-11 + 2x = 4x + 17

Reorder the terms:
-11 + 2x = 17 + 4x

Solving
-11 + 2x = 17 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-11 + 2x + -4x = 17 + 4x + -4x

Combine like terms: 2x + -4x = -2x
-11 + -2x = 17 + 4x + -4x

Combine like terms: 4x + -4x = 0
-11 + -2x = 17 + 0
-11 + -2x = 17

Add '11' to each side of the equation.
-11 + 11 + -2x = 17 + 11

Combine like terms: -11 + 11 = 0
0 + -2x = 17 + 11
-2x = 17 + 11

Combine like terms: 17 + 11 = 28
-2x = 28

Divide each side by '-2'.
x = -14

Simplifying
x = -14

See similar equations:

| 5(x+4)=6(x-6) | | 55x-5y=5.7 | | 100m^8+9= | | 50*1+5+5*10-10= | | 6r+5d-5r= | | (x-8)-(x+6)=9x | | 5/13=y | | 3/5x-78 | | 4x+23=-33 | | 5x+11=4x+4 | | 7(7x-2)=27+8x | | -69+7x=93+x | | -5x-20=-8x+28 | | 4(3x+1)=5x+25 | | 3x+20=2d+40 | | -75+9x=40+4x | | 2x-8=6x+10 | | 35+7x=-7(4-4x) | | -x-17=-3x+9 | | 5n^2-80=-30n | | -53+12x=73+3x | | 35+7a=6(1+6a) | | -2x-5x-4+2x+12=x | | 6x-113=2x-5 | | 3(m+1)-2m=o | | 7x+10=5*(3+x) | | (x+2)(x-7)=18 | | 2y-3(y+1)=(5y+3)+5 | | 0.111y^2=(6y)^(1/2) | | 0.111y^2=(6y)^1/2 | | 6x+3y-10z=100 | | 32+9.90x=91.40 |

Equations solver categories